Pengaruh Perilaku Peternak Plasma Terhadap Kinerja Usaha Kemitraan Ayam Ras Pedaging di Kabupaten Bangli - Wiwekananda, Pande Dwi; Suparta, Nyoman; Antara, Made (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 8 No 1 (2020): MEI 2020DO - 10.24843/JMA.2020.v08.i01.p03, 2020)
Broiler partnership business has been implemented in almost every region in Bali Province. In the development of broiler partnership business, the factors driving farmers to join the partnership pattern are the availability of livestock production facilities, availability of experts, working capital from the core and a guaranteed marketing. Research was conducted in Bangli Regency, the sample size was 77 respondents of broiler breeders spread in Bangli Regency. Data analysis techniques used Smart PLS programs. This study was conducted to analyze the effect of the farmer characteristics, interactions of communication, entrepreneurial spirit and breeder's motivation to breeder behavior, as well as the correlation of behavior and partnership business performance. The results showed that (1) Farmer Characteristics, Interactions of Communication, Farmer Entrepreneurial Soul and Farmer Motivation significantly affected the behavior of broiler breeders in Bangli Regency. (2) Farmer Characteristics, Communication Interaction, Farmer Entrepreneurial Soul and Farmer Motivation have a significant effect on the performance of broiler partnership business in Bangli Regency. (3) Behavior of broiler breeders significantly influences the partnership business performance. This study suggests that the entrepreneurial spirit of breeders, interactions of communication, characteristics of breeders, and breeders' motivations need to be improved, because behavior of breeders and partnership business performance are affected by those factors. Thus, a successful business partnership undertaken by broiler breeders in Bangli Regency can be achieved. Keywords: plasma farmer behavior and partnership business performance